ANALYSIS OF ECONOMIC FACTORS AFFECTING THE GROWTH OF THE PHARMACEUTICAL INDUSTRY AND ITS IMPACT ON LABOUR ABSORPTION IN INDONESIA: A LITERATURE REVIEW - Gunawan Widjaja; Diana Laila Ramatillah; Rio Johan Putra (Adisam Publisher, 2025)
This study aims to analyse the economic factors that influence the growth of the pharmaceutical industry and its impact on employment in Indonesia through a literature review study. The pharmaceutical industry is one of the strategic sectors that continues to grow in line with the increasing public need for health products and government policy support. The study results show that investment, government policies, exchange rate fluctuations, dependence on imported raw materials, and technological innovation are the main economic factors that influence the growth of the national pharmaceutical industry. The growth of this sector has a positive impact on labour absorption, both directly in production and indirectly through supporting sectors such as distribution and research. However, challenges related to the quality of human resources and raw material independence still need to be overcome so that the pharmaceutical industry can contribute more optimally to the economy and job creation in the future.